The influence of aphrodisiac foods in sexual desire: integrative review (Research, Society and Development, 2021)
Certain foods have gained prominence in world cuisine for presenting bioactive compounds with libido-stimulating properties, commonly labeled as aphrodisiac foods. Thus, in addition to the nutritional value of these foods, there is a perspective associated with the sexual well-being of men and women. Therefore, the aim of this study was to analyze published works on the influence of aphrodisiac foods on sexual desire, as well as their effects on adult individuals. The then study is an integrative literature review with a qualitative approach, which performed analysis, identification and description of works, highlighting the importance of future research on the subject. It was possible to observe that foods considered to be aphrodisiacs and their compounds can act by increasing sexual desire, contributing to the improvement of vasodilation and irrigation of Organs sexual organs by the presence of nutrients specifically related to sexual potency, and their consumption is responsible for positively stimulating libido of individuals, such as the micronutrients zinc, magnesium, and B-complex vitamins. These foods were associated with improved libido, arousal, orgasm and some also showed antioxidant and anti-inflammatory action. However, it should be noted that these foods are not miraculous, therefore their consumption must be done respecting the nutritional needs and individualities of people so that they can achieve the desired effects.